Sosialisasi Desa Cerdas (Smart Village) dalam Meningkatkan Literasi Digital Masyarakat Perdesaan: Pengabdian - Sri Karuniari Nuswardhani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Digital literacy disparity in rural areas remains a major obstacle in achieving modern, transparent, and independent village governance. This community service activity aims to improve the digital literacy and skills of Pucangsari Village residents through the socialization of the Smart Village concept. The primary issues identified at the partner location were the low utilization of information technology for public services and a lack of awareness regarding the importance of data security in the digital space. The implementation method consisted of three stages: preparation through needs analysis, interactive socialization regarding the pillars of a Smart Village, and technical assistance in using digital-based village service platforms. The results of this activity showed a significant increase in the participants' digital literacy, measured through pre- and post-activity evaluations. The community now has a better understanding of the importance of technology integration in village governance to accelerate access to information and public services. In conclusion, strengthening digital literacy through the Smart Village model in Pucangsari Village can foster the social and economic transformation of rural communities toward an inclusive digital era.